1997
DOI: 10.1021/om9703550
|View full text |Cite
|
Sign up to set email alerts
|

Silylation of Styrene with Vinylsilanes Catalyzed by RuCl(SiR3)(CO)(PPh3)2 and RuHCl(CO)(PPh3)3

Abstract: The coupling reaction of styrene with vinylsilanes catalyzed by ruthenium complexes was investigated. RuHCl(CO)(PPh3)3 (I) and RuCl(SiR3)(CO)(PPh3)2 (where R3 = Me3 (II), Me2Ph (III), (EtO)3 (IV)) were found to be efficient and selective catalysts for the formation of E-1-phenyl-2-silylethene and evolution of ethene. Stoichiometric reactions of styrene with the Ru−Si bonds of II−IV in argon and silylstyrene with the Ru−H bond in air (I*) as well as a MS study of the product of the deuterated styrene with vinyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 18 publications
4
55
1
Order By: Relevance
“…Studies in the groups of Marcieniec and Fischer have revealed that styrene reacts with vinylsilanes 58a in the pres- ence of ruthenium carbene complex 2 [69] or the ruthenium hydride complex [RuHCl(CO)(PPh 3 ) 3 ] (59) [70] to give the same cross-metathesis product 58b and ethylene (Scheme 15).…”
Section: Activation Of Silanesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the groups of Marcieniec and Fischer have revealed that styrene reacts with vinylsilanes 58a in the pres- ence of ruthenium carbene complex 2 [69] or the ruthenium hydride complex [RuHCl(CO)(PPh 3 ) 3 ] (59) [70] to give the same cross-metathesis product 58b and ethylene (Scheme 15).…”
Section: Activation Of Silanesmentioning
confidence: 99%
“…Cross-metathesis of styrene and vinylsilanes A mechanism for the ruthenium hydride-catalyzed reaction has been proposed (Scheme 16) [70] that involves insertion of the vinylsilane into the RuϪH bond of Q to give the σ-alkyl intermediate R, which undergoes β-silyl elimination to give the RuϪSi intermediate S. Ethylene is displaced by styrene, which inserts into the RuϪSi bond to give a new σ-alkyl intermediate T. β-Hydride elimination regenerates the catalytically active species Q and liberates the vinylsilane 58. Alternatively, catalysts containing RuϪSi bonds can be employed in this reaction; these catalysts give comparable results.…”
Section: Activation Of Silanesmentioning
confidence: 99%
“…
Abstract-Effective cross-metathesis of H 2 C C(H)SiR 3 , where SiR 3 =Si(OMe) 3 , Si(OEt) 3 , Si(OSiMe 3 ) 3 , with selected olefins in the presence of (PCy 3 ) 2 Cl 2 Ru( CHPh) (I) is described. Treatment of p-substituted styrenes, 1-alkenes and selected allyl derivatives H 2 C CHCH 2 R% (R%=SiMe 3 , Si(OEt) 3 , Ph, OPh) with an excess of H 2 C C(H)SiR 3 results in the formation of the respective cross-metathesis products with good yields and selectivities.
…”
mentioning
confidence: 99%
“…2 The reaction, which resembles crossmetathesis, however, proceeds by a non-metallocarbene mechanism involving activation of C H and Si C bonds according to Scheme 1. 3 Unfortunately, the formation of some amounts of isomerization products cannot be avoided when using this method. 4 The development of well-defined, functional group tolerant ruthenium and molybdenum metathesis catalysts has opened new opportunities for applying metathesis in organic synthesis.…”
mentioning
confidence: 99%
“…The mechanism of SC proved by Wakatsuki [8] and by us [9] proceeds by insertion of the vinylsilane into the M-H bond and a β-Si transfer to the metal with elimination of ethylene to generate M-Si species, which is followed by insertion of the alkene into the M-Si bond and a β-H transfer to the metal with elimination of the substituted vinylsilane (Scheme 2). The most synthetically effective results are given in ref.…”
Section: Introductionmentioning
confidence: 98%